Trophic relationships in a deep Mediterranean cold-water coral bank (Santa Maria di Leuca, Ionian Sea) - Carlier, A.; Le Guilloux, E.; Olu, Karine; Sarrazin, Jozee; Mastrototaro, F.; Taviani, M.; Clavier, J. (Marine Ecology Progress Series, 2009)
Cold-water corals (CWC) are frequently reported from deep sites with locally accelerated currents that enhance seabed food particle supply. Moreover, zooplankton likely account for ecologically important prey items, but their contribution to CWC diet remains unquantified. We investigated the benthic food web structure of the recently discovered Santa Maria di Leuca (SML) CWC province (300 to 1100 m depth) located in the oligotrophic northern Ionian Sea. We analyzed stable isotopes (delta C-13 and delta N-15) of the main consumers (including ubiquitous CWC species) exhibiting different feeding strategies, zooplankton, suspended particulate organic matter (POM) and sedimented organic matter (SOM). Zooplankton and POM were collected 3 m above the coral colonies in order to assess their relative contributions to CWC diet. The delta N-15 of the scleractinians Desmophyllum dianthus, Madrepora oculata and Lophelia pertusa (8 to 9 parts per thousand) and the gorgonian Paramuricea cf. macrospina (9 to 10 parts per thousand) were consistent with a diet mainly composed of zooplankton (6 to 7 parts per thousand). The antipatharian Leiopathes glaberrima was more N-15-depleted (7 to 8 parts per thousand) than other cnidarians, suggesting a lower contribution of zooplankton to its diet. Our delta C-13 data clearly indicate that the benthic food web of SML is exclusively fuelled by carbon of phytoplanktonic origin. Nevertheless, consumers feeding at the water-sediment interface were more C-13-enriched than consumers feeding above the bottom (i.e. living corals and their epifauna). This pattern suggests that carbon is assimilated via 2 trophic pathways: relatively fresh phytoplanktonic production for C-13-depleted consumers and more decayed organic matter for C-13-enriched consumers. When the VC values of consumers were corrected for the influence of lipids (which are significantly C-13-depleted relative to other tissue components), our conclusions remained unchanged, except in the case of L. glaberrima which could assimilate a ...